Ca3WO6 prepared by roasting tungsten-containing materials and its leaching performance. (September 2015) - Li, Xiaobin; Xu, Xiangming; Zhou, Qiusheng; Qi, Tiangui; Liu, Guihua; Peng, Zhihong; Cui, Yuanfa; Li, Jianpu
Abstract: Aiming to develop a novel technique to alleviate the environmental stresses caused by waste-water in the prevalent ammonium paratungstate manufacture process, preparation process of tricalcium tungstate (Ca3 WO6 ) from tungsten-containing materials by roasting was studied systematically in this paper. Thermodynamic analyses and experimental results show that Ca3 WO6 could be formed by reactions of CaWO4 /Fe(Mn)WO4 with CaO, Ca(OH)2 or CaCO3 in air. Increasing roasting temperature not only accelerates the conversion of CaWO4 to Ca3 WO6 but also eliminates the dependence of the conversion on calcium compound types. Moreover, additive CaF2 can greatly reduce roasting temperature for complete conversion of tungsten-containing minerals in mixed concentrate of scheelite and wolframite to Ca3 WO6 . Additionally, Ca3 WO6 clinker prepared by mixed concentrate has good leachability in aqueous ammonium carbonate solution with WO3 recovery of 98.4%. The work presented is favorable for developing a promising technique with recycling both auxiliary materials and solutions for cleaner production of ammonium paratungstate. Highlights: Ca3 WO6 was synthesized by reactions of CaWO4 /Fe(Mn)WO4 with CaO, Ca(OH)2 or CaCO3 . Additive CaF2 could greatly reduce the roasting temperature for preparing Ca3 WO6 . The optimal conditions for synthesizing Ca3 WO6 were determined. Ca3 WO6 had good leaching performance in aqueous ammonium carbonate solution.